2020
DOI: 10.4178/epih.e2020011
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the reproductive number and the outbreak size of COVID-19 in Korea

Abstract: Therefore, our objective was to estimate the reproduction number (R) and evaluate the effectiveness of preventive measures. METHODS:A COVID-19 transmission model (SEIHR) was established to suit the Korean outbreak. The number of daily confirmed cases in Daegu and North Gyeongsang Province (NGP), the main area of outbreak, was used. The first patient' symptom onset date in the Daegu/NGP outbreak was assumed as January 22, 2020. The R according to the start date of the effect of preventive measures was estimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
224
3
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(240 citation statements)
references
References 5 publications
5
224
3
8
Order By: Relevance
“…However, the complex simulation models that estimate mortality outcomes require numerous assumptions and, perhaps more importantly, are inaccessible to most. [12][13][14][15][16] In contrast, our approach utilizes public data published daily by the WHO and population-level clinical data that countries already collect. 17 Our approach can be readily applied to other countries and will directly account for differences in the age distribution of populations, which is integral for calculating an accurate mortality burden as infected older adults may be more likely to die than infected middle-aged adults from COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…However, the complex simulation models that estimate mortality outcomes require numerous assumptions and, perhaps more importantly, are inaccessible to most. [12][13][14][15][16] In contrast, our approach utilizes public data published daily by the WHO and population-level clinical data that countries already collect. 17 Our approach can be readily applied to other countries and will directly account for differences in the age distribution of populations, which is integral for calculating an accurate mortality burden as infected older adults may be more likely to die than infected middle-aged adults from COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…5 It is therefore crucial that world leaders mount effective public health measures to limit human-tohuman transmission, including hand hygiene, social distancing and self-isolation. 1,6,7 Twitter may represent a powerful public health tool for world leaders to rapidly and directly communicate information on COVID-19 to citizens, in addition to more conventional media such as television, radio and newspapers. Twitter is a free microblogging social media website with 152 million registered daily users.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies indicated that the most probable basic reproductive number (R 0 ) is between two and four for the coronavirus (meaning that each infectious individual may directly generate two to four others) [1][2][3][4][5][6] . However, some estimates suggested R 0 higher than four with confidence intervals that reach values close to eight 2,7 . A reproductive number higher than one implies a progressive increase in cases, which translates into epidemics.…”
Section: Introductionmentioning
confidence: 98%